Analysis of the Meaning and Function of Huler Wair Ceremony in Waiara Village, Kewapante District Sikka Regency - Agustina Yuliovi; Darmawan Darmawan; Antonius M. K. Naro (Jurnal Ilmu Sosial dan Humaniora, 2026)
This research is titled "analysis of the meaning and function of the huler wair ceremony, kewapante sub-district, sikka district". The formulation of the problem in this study (1) what is the meaning of “huler wair” ceremony in waiara village, kewapante district, sikka regency? (2) what is the function of “huler wair” ceremony in waiara village, kewapante district, sikka regency? In this study using qualitative methods and data collection in this research is done by observation, interviews, and documentation. The data that has been collected is analyzed descriptively, namely (1) collecting data (2) selecting data (3) reviewing data (4) drawing conclusions in the form of functions and meanings at the huler wair ceremony analysis in the discussion of this research, it is concluded that the meaning of the huler wair ceremony in Waiara village, the function of the huler wair ceremony in Waiara village and the function of idioms as a function of hope and advice.